(untitled) (Research, Society and Development, 2020)
The objective of this research was to characterize the clinical profile and identify the risk factors associated with the possibility of developing cardiovascular diseases in military police. A descriptive research was carried out, quantitative, with cross-section, participated 54 military police of the 3rd Military Police Battalion, in the municipality of Santarém, state of Pará, being carried out by applying a structured form with closed questions, evaluation of sociodemographic data, anthropometric parameters, physiological and biochemicals, and cardiovascular risk stratification using the Framingham risk score. In addition, there was an association and correlation between variables not included in the Framingham risk score. The sample was characterized by 91% male, where the majority were in the age group of 30-49 years. The following changes in the evaluated factors were found: 2% were smokers, 65% with dyslipidemia, 30% with hyperglycemia, 20% with physical inactivity and 82% with overweight and obese. Of the total sample, 75% were at low risk for cardiovascular risk, however, with altered anthropometric parameters. There was a positive and significant correlation between the cardiovascular risk rate by the Framingham risk score with the body mass index and the abdominal circumference. The study showed that the sample of military police officers has low cardiovascular risk, however, the altered anthropometric parameters correlated with the possible increased risk of morbidity and mortality of cardiovascular diseases.